2013
DOI: 10.4161/dish.27085
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in disaster preparedness between racial/ethnic groups

Abstract: Objective The objective of this study was to examine the association between race/ethnicity (including language subgroups among Hispanics) and disaster preparedness among Behavioral Risk Factor Surveillance System (BRFSS) survey respondents.Methods BRFSS data were obtained for eight states which implemented the optional general preparedness module from 2006 through 2010. Three dependent variables were analyzed including presence of four preparedness items (i.e., food, water, flashlight, and radio), emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Webb et al (2002) found a significant effect for business owners' risk perception on their business disaster preparedness activities, but also found ethnicity to have no significant influence on those business preparedness activities. Webb et al's (2002) findings indicate a propensity for non-white owners to prepare more for disasters, while Bethel et al (2013) found no disparity between general preparedness of ethnic minority groups and whites. Hocker (2005) reported that African-American businesses are more likely to fail than other businesses, with nearly two-thirds being in the retail and service sectors.…”
Section: Race/ethnicity Of Ownermentioning
confidence: 90%
“…Webb et al (2002) found a significant effect for business owners' risk perception on their business disaster preparedness activities, but also found ethnicity to have no significant influence on those business preparedness activities. Webb et al's (2002) findings indicate a propensity for non-white owners to prepare more for disasters, while Bethel et al (2013) found no disparity between general preparedness of ethnic minority groups and whites. Hocker (2005) reported that African-American businesses are more likely to fail than other businesses, with nearly two-thirds being in the retail and service sectors.…”
Section: Race/ethnicity Of Ownermentioning
confidence: 90%
“…In relation to socio-economic status, Whittaker et al (2005) and Dunlap and Mertig (1995) suggested that affluence is not always a determining factor for environmental concern and a conservation ethos. Further, Bethel et al (2013) found that the difference in disaster preparedness (measured by medication supplies) in eight states in the USA was not due to factors related to socio-economic status. Particularly for this investigation, socio-economic status was not considered to be one of the most relevant factors.…”
Section: The Concept Of Social Responsibility and Community Resiliencementioning
confidence: 97%
“…Hispanics suffered more from psychological distress after California earthquakes and the 9/11 terrorist attacks [39]. Spanish-speaking Hispanics are less likely to have an emergency evacuation plan, and racial/ethnic minorities are less likely to have medication supplies [40]. Fothergill et al indicate that community isolation and cultural insensitivities also make racial/ethnic minorities in the US more vulnerable to natural disasters [41].…”
Section: Literature Review: Social Vulnerability and Inequalitymentioning
confidence: 99%